1996
DOI: 10.3109/00016359609003553
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of the Carabelli trait in twins discordant or concordant for cleft lip and/or palate

Abstract: The frequency and expression of the Carabelli trait among 36 twin pairs discordant or concordant for cleft lip and/or palate were investigated. Four of 10 monozygotic (MZ) and 24 of 26 dizygotic (DZ) pairs of twins were discordant for clefts. The frequency of the trait on the first upper molars of the noncleft subjects was 79%. It varied from 54% to 61% in the subjects with clefts, and the frequency of the trait decreased with increasing extension of the cleft. The occurrence of the trait was bilateral in more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…This aspect of sample composition might also explain why the relationship between Carabelli's trait expression and RICD was not significant when Carabelli's trait expression was quantified under the three-state system. Previous work has indicated that there is some genetic component to Carabelli's trait variation (Alvesalo et al, 1975;Boraas, Messer, & Till, 1988;Goose & Lee, 1971;Kieser, 1984;Laatikainen & Ranta, 1996;Townsend & Martin, 1992) and that prevalence varies between populations (Dahlberg, 1951;Irish, 1997;Kraus, 1951;Meredith & Hixon, 1954;Scott, 1980;Townsend & Brown, 1981;Tsuji, 1958;Turner, 1967). That the relationships detected by this study were not as strong as those reported in previous work that focused on a single bioregional sample suggests that underlying gene expression-which may differ between populations-affects Carabelli's trait expression.…”
Section: Discussionmentioning
confidence: 99%
“…This aspect of sample composition might also explain why the relationship between Carabelli's trait expression and RICD was not significant when Carabelli's trait expression was quantified under the three-state system. Previous work has indicated that there is some genetic component to Carabelli's trait variation (Alvesalo et al, 1975;Boraas, Messer, & Till, 1988;Goose & Lee, 1971;Kieser, 1984;Laatikainen & Ranta, 1996;Townsend & Martin, 1992) and that prevalence varies between populations (Dahlberg, 1951;Irish, 1997;Kraus, 1951;Meredith & Hixon, 1954;Scott, 1980;Townsend & Brown, 1981;Tsuji, 1958;Turner, 1967). That the relationships detected by this study were not as strong as those reported in previous work that focused on a single bioregional sample suggests that underlying gene expression-which may differ between populations-affects Carabelli's trait expression.…”
Section: Discussionmentioning
confidence: 99%
“…By comparison, quantitative genetic analyses of human dental data have been limited, especially concerning crown variation of the postcanine dentition. Most previous studies have focused on overall crown size (e.g., Alvesalo & Tigerstedt, ; Dempsey & Townsend, ; Townsend & Brown, , , ; Townsend et al, ; Stojanowski, Paul, Seidel, Duncan, & Guatelli‐Steinberg, ) or specific features such as Carabelli's trait (Alvesalo, Nuutila, & Portin, ; Biggerstaff, ; Harris & Bailit, ; Laatikainen & Ranta, ; Townsend & Martin, ) or cusp 5 of the maxillary molars (Harris & Bailit, ; Townsend, Yamada, & Smith, ). However, comprehensive assessments of a more complete suite of postcanine crown variants, such as that presented in the Arizona State University Dental Anthropology System (ASUDAS) (Turner II, Nichol, & Scott, ) is lacking (but see Scott & Potter, ).…”
Section: Introductionmentioning
confidence: 99%
“…Results of quantitative genetic analyses have shown permanent crown dimensions to be under moderate to strong genetic influence, with additive genetic variance accounting for over half of phenotypic variance on average (e.g., Alvesalo & Tigerstedt, ; Dempsey & Townsend, ; Dempsey, Townsend, Martin, & Neale, ; Lundström, ; Stojanowski et al, ; Townsend & Brown, ). By comparison, morphological characters on adult teeth yield lower heritability estimates, typically falling within the 0.40 to 0.80 range for the mesial‐most member of each tooth class (e.g., see Berry, ; Laatikainen & Ranta, ; Mizoguchi, ; Townsend & Martin, ; Scott & Turner, , p. 164). It is important to note that not all studies employ the same analytical methods and that heritability estimation has improved in statistical rigor over the years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some morphological features have been well studied within a quantitative genetic framework—primarily Carabelli's cusp (e.g., Alvesalo, Nuutila, & Portin, ; Biggerstaff, ; Laatikainen & Ranta, ; Scott & Potter, ; Townsend & Martin, )—most crown traits have few published heritability estimates, and no studies have been published applying robust, model‐fitting approaches such as maximum likelihood variance components analysis to complex pedigree structures that, in many cases, more closely approximate the composition of ancient populations and archaeological samples. This, despite proof of concept of the validity of these methods for use with binary variables (e.g., Carson, ; Duggirala, Mitchell, Blangero & Stern, ; Horimoto et al, ).…”
Section: Introductionmentioning
confidence: 99%